Correlation Between Duration of Docetaxel Administration and Epiphora Severity in Nasopharyngeal Carcinoma Patients - Riani Erna; Rafika Sidharta; Denny Satria Utama; Debby Handayati Harahap (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Docetaxel, an effective chemotherapeutic agent for various cancers, including nasopharyngeal carcinoma, is associated with epiphora as a notable adverse effect. Objective: This study aimed to investigate the correlation between the duration of docetaxel administration and the severity of epiphora, as assessed by the Munk score, in patients with nasopharyngeal carcinoma. Methods: A descriptive cross-sectional study was undertaken at the Ophthalmology Polyclinic of Dr. Mohammad Hoesin Hospital, Palembang, from January to August 2024. The study sample comprised n=25 patients who met the research criteria. Epiphora severity was measured using the Munk score. Statistical analysis was performed using Spearman’s rank correlation test. Results: The majority of patients were male (68.2%) and aged ≤50 years (77.3%). Most received an 80 mg docetaxel dose (91%) for six weeks (77.3%). Based on the Munk score, 86.4% of patients had a score of 1, and 13.6% had a score of 2. No significant associations were found between Munk score and gender (p=0.445), age (p=0.578), or docetaxel dose (p=1.000). However, the duration of docetaxel administration was significantly associated with Munk score (p=0.001) and showed a moderate positive correlation with epiphora severity (r=0.626; p=0.001). Conclusion: Patients with a Munk score of 2 received docetaxel for a longer duration. A longer duration of docetaxel administration is associated with a higher Munk score for epiphora in nasopharyngeal carcinoma patients.